2021
DOI: 10.1016/j.pnpbp.2021.110262
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-seeking behaviour is differentially expressed in male and female mice exposed to maternal separation and is associated with alterations in AMPA receptors subunits in the medial prefrontal cortex.

Abstract: Impulsivity is a key trait in the diagnosis of major depressive disorder (MDD) and substance use disorder (SUD). MDD is a chronic illness characterized by sadness, insomnia, and loss of interest. SUD is a chronic and relapsing disorder characterized by the consumption of drugs despite their negative consequences. Among drugs of abuse, cocaine is the most consumed psychostimulant. Animal studies demonstrated that increased impulsivity predicts predisposition to acquire cocaine self-administration (SA) behaviour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…MSEW causes an impairment of cocaine-induced behavioral sensitization, possibly due to a dysfunction of the dopaminergic system, a potential vulnerability factor for the development of substance use disorders ( Gracia-Rubio et al, 2016 ). In addition, mice exposed to MSEW expressed higher cocaine intake, an enhanced vulnerability to the acquisition of cocaine self-administration, and an incapacity for this behavior to be extinguished ( Castro-Zavala et al, 2020 ; Castro-Zavala et al, 2021a ; Castro-Zavala et al, 2021b ). In the CPP paradigm, MS (3h/day, from PND2 to PND14-15) also increased vulnerability to cocaine reward in adolescent rats ( Alves et al, 2020 ) and mice ( Viola et al, 2016 ), suggesting that this early life stress subsequently enhances the motivational salience of stimuli associated with cocaine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSEW causes an impairment of cocaine-induced behavioral sensitization, possibly due to a dysfunction of the dopaminergic system, a potential vulnerability factor for the development of substance use disorders ( Gracia-Rubio et al, 2016 ). In addition, mice exposed to MSEW expressed higher cocaine intake, an enhanced vulnerability to the acquisition of cocaine self-administration, and an incapacity for this behavior to be extinguished ( Castro-Zavala et al, 2020 ; Castro-Zavala et al, 2021a ; Castro-Zavala et al, 2021b ). In the CPP paradigm, MS (3h/day, from PND2 to PND14-15) also increased vulnerability to cocaine reward in adolescent rats ( Alves et al, 2020 ) and mice ( Viola et al, 2016 ), suggesting that this early life stress subsequently enhances the motivational salience of stimuli associated with cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…No studies have been performed about the inoculating effect of MS on the subsequent response of stressed animals to drugs of abuse. However, studies of the mechanisms than underlie the effects of more stressful protocols of MS on the rewarding properties of cocaine have revealed that MS modifies the activity of AMPA and NMDA receptors in structures of the brain reward circuit and other areas involved in the learning of cocaine-cue association ( Ganguly et al, 2019 ; Castro-Zavala et al, 2020 ; Castro-Zavala et al, 2021b ). MSEW was seen to enhance glutamatergic function in the nucleus accumbens and increase excitability of ventral tegmental area DA neurons ( Castro-Zavala, et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, cumulative evidence has proved biologically based sex differences in all phases of drug addiction (for all drugs in general, but including cocaine; e.g., Becker and Chartoff 2019 ), exhibiting females a more rapid escalation from casual drug taking to addiction, a greater withdrawal response with abstinence (i.e., increased negative affect), and a tendency for a negative treatment outcome (reviewed in Becker and Koob 2016 ). Moreover, while stress exposure early in life is a well-accepted risk factor for modeling mood disorders in rodents, and having a prior psychiatric vulnerability is also a key trigger for drug consumption (e.g., self-treatment to manage negative affect; Levis et al 2021 ), the combination of both risk factors has proven to induce different responses between sexes (e.g., Alves et al 2020 ; Castro-Zavala et al 2020 , 2021 ; Levis et al 2021 ). One of the simplest models to mimic a depressive-like phenotype in rodents by early-life stress applies a single episode (24 h) of maternal deprivation on postnatal day (PND) 9 (Ellenbroek et al 1998 ), since it interferes with their normal brain developmental trajectories and modifies their behavioral and neurochemical outcomes (reviewed in Marco et al 2015 ; also see our results in García-Cabrerizo et al 2020 ; Bis-Humbert et al 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…The cocaine SA paradigm was conducted as previously described [39][40][41] . Nosepoking into the active hole resulted in a cocaine infusion (0.75 mg/kg/infusion) and nosepoking into the inactive hole had no consequences.…”
Section: Cocaine Self-administration (Sa)mentioning
confidence: 99%